The Influence of Visionary Leadership and Compensation on Achievement Motivation and Its Impact on Lecturer Performance (Case Study of A Private Islamic Religious College In Metro Lampung City) - Supriani, Yuli; Wahidin, Unang; Nursobah, Asep; Syamsul Arifin, Bambang; Mahmud, Mahmud (Lafadz Jaya Publisher, 2024)
This research was motivated by the low performance of lecturers at Private Islamic Religious Universities in Metro City, Lampung, with indicators of minimal scientific publications, lack of interest in community service activities, and lack of commitment to research. These problems include ineffective visionary leadership, an inadequate compensation system, and lecturers' achievement motivation that is not aligned with their main duties. This research aims to determine the effect of visionary leadership and compensation on the performance of lecturers with achievement motivation as an intervening variable at Private Islamic Religious Universities in Metro Lampung City. This research uses a quantitative approach with path analysis techniques and uses survey methods. The research results show: First, visionary leadership has a positive and significant effect on achievement motivation. Second, compensation has a positive and significant effect on achievement motivation. Third, visionary leadership has a positive and significant effect on lecturer performance. Fourth, compensation has a positive and significant effect on lecturer performance. Fifth, achievement motivation has a positive and significant effect on lecturer performance. Sixth, visionary leadership is positive and significant for lecturer performance through achievement motivation. Seventh, compensation has a positive and significant effect on lecturer performance through achievement motivation.